1991
DOI: 10.1021/j100175a072
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the geometry of the excited state of vanadium oxides anchored onto silica and their photoreactivity toward carbon monoxide molecules

Abstract: The phosphorescence spectrum of vanadium oxide anchored onto Si02 shows well-resolved vibrational fine structure at 77 K. Franck-Condon analysis of the phosphorescence indicates that the internuclear equilibrium distance between oxygen and vanadium ions of V=0 vanadyl groups as emitting sites of V/Si02 catalyst anchored onto Si02 is larger by 0.12 A in its charge-transfer excited triplet state than in its ground state. UV irradiation of the catalyst in the presence of CO leads to the formation of C02 (photored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…The related peaks positions are labeled in the figure. According to previous literatures [80], [81], the vibrational fine structures are usually caused by the V = O vanadyl group involved in a tetrahedral coordination. Previous studies reported that the fine features of PL spectra for V 2 O 5 were prominent at low temperature experiment.…”
Section: Zno/v2o5 Bilayermentioning
confidence: 88%
“…The related peaks positions are labeled in the figure. According to previous literatures [80], [81], the vibrational fine structures are usually caused by the V = O vanadyl group involved in a tetrahedral coordination. Previous studies reported that the fine features of PL spectra for V 2 O 5 were prominent at low temperature experiment.…”
Section: Zno/v2o5 Bilayermentioning
confidence: 88%
“…Analysis of the intensity distribution in the progression yields that the excited state has expanded 0.12 A relative to the ground state. This plays an important role in photoreactions using SiO2-V as a catalyst [57].…”
Section: Luminescence Of Transition Metal Ionsmentioning
confidence: 99%
“…ions, which results in the formation of pairs of hole centres (O -) and trapped electrons (V 4? ) as well as a reverse radiative decay by disappearance of hole-electron pair (Patterson et al 1991). Frank-Condon analysis indicates that the inter-nuclear equilibrium distance between the vanadium and oxygen ions during the charge transfer process in excited state is larger by 0.012 nm than that in its ground state.…”
Section: Resultsmentioning
confidence: 91%
“…Several articles reported the visible light emission of vanadium oxide supported on different metal oxides upon excitation (Anpo 1980;Patterson et al 1991;Iwamoto et al 1983;Garcia et al 2000). It has been found that V = O vanadyl groups are the most active sites for the PL emission; the position of the emission band depends on the carriers and contents in various supported vanadium oxides (Iwamoto et al 1983).…”
Section: Resultsmentioning
confidence: 99%